A reconfigurable damage-tolerant controller based on a modal double-loop framework. (1st May 2017) - Genari, Helói F.G.; Mechbal, Nazih; Coffignal, Gérard; Nóbrega, Eurípedes G.O.
Abstract: Active vibration control of flexible structures has received considerable attention in the latest decades. However, several related control problems remain open to new investigations such as robust performance, spillover instability, and structural changes due to damage. Specifically in the case of damage, it may significantly aggravate closed-loop performance. Damage-tolerant active control is a recent research area that includes structural damage effect reduction in the controller design requirements. This paper presents a novel control method based on a modal double-loop controller design, aiming for vibration reduction of noncollocated flexible structures subject to damage and encompassing online reconfigurability. The first controller is designed for the healthy system in order to comply with predefined performance and robustness requirements, based on modal H ∞ norm. The second controller complements the closed-loop performance if the structure is damaged. A reconfigurable modal technique is adopted to design the second controller, using online modal structural parameter change information to update the controller. To assess the proposed method, finite element models are developed for a case study structure, including health and damage conditions. Results show the effectiveness of the methodology along with performance improvement compared to single-loop controllers based on regular H ∞ and modal H ∞ approaches. Abstract : Highlights: A modal double-loop novel control framework is proposed to face damage on structure. The strategy merges structural health monitoring and active control methods. A modal H ∞ controller ensures performance and robustness to the healthy structure. A new modal state-tracking controller is reconfigured online to face damage. Method simulations show efficient modal energy selectivity to face damage.